Pengaruh Faktor-Faktor Internal Dan Faktor Makroekonomi Terhadap Pangsa Pasar (Market Share) Bank Syariah Indonesia - anik anik; Salmia Salmia; Iin Emy Prastiwi (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to determine the effect of internal and macroeconomic factors on the market share of Islamic banks in Indonesia. The internal factors in this study are Third Party Funds (DPK), Return on Assets (ROA), and Non Performing Financing (NPF), while the macroeconomic factor is the rupiah exchange rate against the dollar. This research is a quantitative research with the object of research on Islamic banking in Indonesia. Market Share, TPF, ROA, NPF data are taken from the report. The population in this study is all financial statements of Islamic banking in Indonesia. The sample in this study is the monthly report of Islamic banking in 2015-2019. The analysis technique in this study uses multiple linear regression analysis. The results in this study are ROA and DPK variables have a significant effect on the market share of Islamic banking in Indonesia. Meanwhile, the NPF variable and the macroeconomic variable, namely the exchange rate, have no significant effect on the market share of Islamic banking in Indonesia.